Overview of Patient Satisfaction to Sharia Services Hospitals in Indonesia: Literature Review - Virgi Mayang Maharani; Sutopo Patria Jati; Sri Achadi Nugraheni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Indonesia has the largest Muslim population in the world, with a high demand for sharia-based service markets. National development planning related to the halal market in Indonesia will open new opportunities and options for people in choosing a product, one of which is the search for health services in hospitals. This increase in demand and opportunity must be followed by good service quality. One indicator of the quality of health care is patient satisfaction. This research aims to determine patient satisfaction with sharia or Islamic health services received and the potential for developing Shariah services in hospitals. This study is a literature review with an electronic database search published 2017-2022 and meets inclusion criteria. Seven articles show that patients are satisfied with Shariah or Islamic health services in hospitals in Indonesia. Investment in human resources, development, and further research into Sharia certification in hospitals needs to be done.  Abstrak: Indonesia memiliki penduduk Muslim terbanyak di dunia, dengan demand terhadap pasar pelayanan berbasis syariah yang tinggi. Perencanaan pengembangan nasional terkait dengan pasar halal di Indonesia akan membuka kesempatan dan opsi baru bagi masyarakat dalam memilih suatu produk, salah satunya adalah pencarian pelayanan kesehatan di rumah sakit. Peningkatan permintaan dan kesempatan ini harus diikuti dengan kualitas pelayanan yang baik. Salah satu indikator kualitas pelayanan kesehatan adalah kepuasan pasien. Penelitian ini bertujuan untuk mengetahui kepuasan pasien terhadap pelayanan kesehatan syariah atau islami yang diterima dan potensi pengembangan pelayanan syariah di rumah sakit. Penelitian ini adalah literature review dengan pencarian database elektronik  yang diterbitkan 2017-2022 dan memenuhi kriteria inklusi. Tujuh artikel menunjukkan bahwa pasien puas terhadap pelayanan kesehatan syariah atau islami di rumah sakit di Indonesia. Investasi sumber daya manusia, pengembangan dan penelitian lebih lanjut terhadap sertifikasi syariah di rumah sakit perlu dilakukan.